2005
DOI: 10.1021/bm050187s
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Poly(hydroxyalkanoates) as a Source of Chiral Hydroxyalkanoic Acids

Abstract: Polyhydroxyalkanoates (PHA) are polyesters of various hydroxyalkanoates accumulated in numerous bacteria. All of the monomeric units of PHA are enantiomerically pure and in R-configuration. R-Hydroxyalkanoic acids can be widely used as chiral starting materials in fine chemical, pharmaceutical and medical industries. In this study, we established an efficient method for the production of chiral hydroxyalkanoic acid monomers from PHA. Pseudomonas putida cells containing PHA were resuspended in phosphate buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 38 publications
6
105
1
1
Order By: Relevance
“…Based on reports that the in vivo hydrolysis of PHA and the secretion of 3-hydroxyalkanoic acids by different bacteria can be efficient at a pH level of 10 to 11 (30,42) or at a pH level of 3 to 4 (24), cells were washed to limit the source of secreted 3HB to intracellularly accumulated PHB and resuspended in the same volume of 0.1 M of potassium phosphate buffer (pH 7), morpholineethanesulfonic acid-NaOH buffer (pH 4), or Tris-HCl buffer (pH 10). After cell-free samples were incubated at 30°C, they were analyzed for secreted 3HB.…”
Section: Methodsmentioning
confidence: 99%
“…Based on reports that the in vivo hydrolysis of PHA and the secretion of 3-hydroxyalkanoic acids by different bacteria can be efficient at a pH level of 10 to 11 (30,42) or at a pH level of 3 to 4 (24), cells were washed to limit the source of secreted 3HB to intracellularly accumulated PHB and resuspended in the same volume of 0.1 M of potassium phosphate buffer (pH 7), morpholineethanesulfonic acid-NaOH buffer (pH 4), or Tris-HCl buffer (pH 10). After cell-free samples were incubated at 30°C, they were analyzed for secreted 3HB.…”
Section: Methodsmentioning
confidence: 99%
“…After the release from cells, they can be processed to a marketable form, e.g. to granulates, and used as sustainable biodegradable substitutes for a variety of "classical" petrochemical plastics such as poly(ethylene) (PE), poly(propylene) (PP), poly(ethlyleneterephtalate) (PET) and many others (Reddy et al, 2003;Khanna & Srivastava, 2005;Ren et al, 2005;Chen, 2009). According to calculations accomplished by Akiyama et al (2003), Harding et al (2007), Pietrini et al (2007), and Titz et al (2012), the production of PHAs should be more beneficial if considering full cradle-to-gate life cycle analysis (LCA) than the production of the petrochemical plastics mentioned before.…”
Section: Composition and Production Of Phasmentioning
confidence: 99%
“…Hydrolysis of PHA to the monomers generally results in a rich source of chiral synthons that can be used as starting materials for synthesis of fine chemicals and marketable products such as pheromons, aromatics, vitamins or antibiotics, or can even be used as pharmaceutically active compounds (Ren et al, 2005). It was demonstrated that 3HB and its oligomers reveal therapeutic effects.…”
Section: The Broad Field Of Potential Applications Of Phasmentioning
confidence: 99%
“…Although these substrates have generated PHA contents of 48 to 77% of cell dry weight (cdw), they are costly, edible and are therefore not competitive for industrial-scale production of PHA [8][9][10][11]. With high gross operating expenses and the resulting cost of PHA at ca.…”
Section: Introductionmentioning
confidence: 99%